Chemical reaction, radiative heat and mass transfer impact on unsteady MHD flow past a porous vertical plate with heat source and dissipation - Kurma Santhosha; B. Shankar Goud; Kottakkaran Sooppy Nisar (Results in Engineering)
The present study examines combined heat and mass transfer in the unsteady MHD natural convection of a viscous fluid within a porous medium, taking into account thermal radiation and chemical reaction effects. The uniform motion of a vertical plate initiates the flow. With an appropriate similarity transformation, the governing equations are then modelled and expressed as a system of partial differential equations. The solution of linear partial differential equations is solved using the finite difference method (FDM) by providing a discretization of the partial differential equation into algebraic equations. It is efficient in the sense of converging quickly to limiting solutions that satisfy the underlying governing equations and related initial and boundary conditions. The influence of several flow factors is graphically analysed. The numerical values for skin friction, Nusselt number, and Sherwood number have been provided. The comparison with existing original research demonstrates a strong connection with the present results, highlighting the methodology of the stated approach. Also, the velocity of the flow is reduced by the increasing values of magnetic field parameters but it improves as the permeability increases and when M increased between 1 and 4 there was a 69 % reduction in velocity. The temperature field reduced as the Prandtl number increased, i.e temperature reduced by 96 % as Pr varied between 0.71 and 10. Moreover, the concentration profiles were enhanced as the Soret number increased, i.e. with Sr varying between 1 to 4 there was a 70.04 per cent increase in Concentration.